Shoulder joint kinetics of the elite wheelchair tennis serve - Reid, M.; Elliott, B.; Alderson, J. (British Journal of Sports Medicine, 2007)
Background: The shoulder is a key joint in wheelchair locomotion and commonly implicated in injury among virtually all wheelchair populations. In tennis, quantification of the shoulder joint kinetics that characterise the wheelchair serve could enhance injury prevention and rehabilitation practices as well as assist coaches evaluate the efficacy of their current technical instruction.